Assessment of the Aluminium Profiles Surface Condition during the Extrusion Process - C. Jasiński; Ł. Morawiński; A. Kochański (Archives of Metallurgy and Materials, 2025)
Correct production of aluminium profiles requires optimising many parameters on the production line. Irregularities in the process cause, among others, unfavourable changes in the surface geometry structure (SGP) of the profile, including roughness. Therefore, assessing surface roughness makes it possible to identify abnormalities in the production process. An original vision system was proposed to analyse changes in the profile surface roughness during the extrusion process. The constructed system, placed on the production line, consists of a monochromatic camera and prototype illumination that enable recording profiles of various shapes. The system allows for quick detection of changes in the quality of the profile surface based on the analysis of reflected light distribution. The work presents, among others, a comparison of vision measurement results obtained during extrusion with the process parameters recorded on the production line.